Rituximab in Lymphoma and Chronic Lymphocytic Leukaemia: A Practice Guideline. Issue 1 (January 2017) - Prica, A.; Baldassarre, F.; Hicks, L.K.; Imrie, K.; Kouroukis, T.; Cheung, M.; ,
Abstract: Rituximab is the first monoclonal antibody to be approved for use by the US Food and Drug Administration in cancer. Its role in the treatment of non-Hodgkin lymphoma, including chronic lymphocytic leukaemia (CLL), has evolved significantly. We aimed to systematically review and update the literature on rituximab in lymphoma and CLL, and provide evidence-based consensus guidelines for its rational use. Validated methodology from the Cancer Care Ontario Program in Evidence-based Care was used. A comprehensive literature search was completed by a methodologist from the Hematology Disease Site Group of Cancer Care Ontario. Data were extracted from randomised controlled trials of rituximab-containing chemotherapy regimens for patients with lymphoma or CLL. Fifty-six primary randomised controlled trials were retrievable and met all inclusion criteria. Clinically important benefits in progression-free survival or overall survival were seen in the following settings: (i) addition of rituximab to combination chemotherapy for initial treatment of aggressive B-cell lymphomas, including diffuse large B-cell lymphoma, Burkitt lymphoma and HIV-related lymphoma with CD4 count ≥50/mm 3 ; (ii) addition of rituximab to combination chemotherapy for initial and subsequent treatment of follicular lymphoma and other indolent B-cell lymphomas; (iii) use of rituximab maintenance in patients with indolent B-cell lymphomas who have responded to chemoimmunotherapy; (iv) addition of rituximab to fludarabine-based chemotherapy or chlorambucil for initial treatment of CLL. The consensus opinion of the Hematology Disease Site Group is that rituximab is recommended for these indications. Highlights: Rituximab leads to clinically important benefits in progression-free survival or overall survival in the following settings: Addition to combination chemotherapy for initial treatment of aggressive B-cell lymphomas. Addition to combination chemotherapy for initial and subsequent treatment of follicular lymphoma and other indolent B-cell lymphomas. Use as maintenance in patients with indolent B-cell lymphomas who have responded to chemo-immunotherapy. Addition to fludarabine-based chemotherapy or chlorambucil for initial treatment of chronic lymphocytic leukaemia.